Studi Kritik Pemikiran Tan Malaka tentang Logika Mistika dalam Madilog Perspektif Hadis - Subagja, Suni (Jurnal Riset Agama, 2024)
Tan Malaka in Madilog mentions mystical logic as the main factor in the Indonesian nation's lack of progress. Mystical logic is an instant way of thinking that cannot be justified. He mentioned mystical logic as an implication of mystical religious teachings. Looking at the context in Indonesia, the religion that is the majority is Islam. So in conclusion, Tan Malaka thinks that mystical logic is the fruit of Islamic religious teachings. Departing from this background, this research wants to examine how the hadith view of mystical logic in Tan Malaka's Madilog is reviewed by ma'anil hadith. This research uses a descriptive qualitative method based on library studies. Based on the hadith analysis approach, Tan Malaka's thought is wrong in concluding that mystical logic is derived from Islam. The study of hadith criticism considers that drawing conclusions with mystical logic methods is prohibited by the Prophet. Like the phenomenon of the Companions who were reprimanded when they argued that the solar eclipse occurred because of the death of Ibrahim, referring to the hadith narrated by Imam al-Bukhari No. 1042. In the Hadith, the Prophet emphasized that there is no connection between natural phenomena and the death of a human being. The second example that is more relevant in contemporary times is the zodiac predictions that have become a trend and are considered commonplace. There are 11 traditions found in this regard, one of which is Sunan Abu Daud's Hadith No. 3406. The Prophet explains that studying the zodiac is considered a forbidden activity because it is included in shirk. The same applies to the prohibition of wearing green clothes on the South Beach. Of course, this is not part of faith and is not sourced from the Qur'an and Hadith.